2022
DOI: 10.3390/jcm11113094
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Effect of COVID-19 Disease Severity on Risk of Diabetes Incidence and the Near 1-Year Follow-Up Outcomes among Postdischarge Patients in Wuhan

Abstract: We assessed the nearly 1-year health consequences following discharge and related risk factors of COVID-19 infection and further explored the long-term effect of COVID-19 disease severity on the risk of diabetes incidence. This prospective study included 248 COVID-19 patients discharged from Wuhan Hospital of Traditional Chinese Medicine who were followed up between Mar 1 and June 10, 2021. Logistic regression models were used to evaluate risk factors. The top ten symptoms were shortness of breath (30.3%), sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
0
16
0
1
Order By: Relevance
“…We identified 4710 records through PubMed, EMBASE, and ScienceDirect database searches. A total of 51 articles (i.e., 33,573 patients) were selected for analysis based on the inclusion and exclusion criteria [ 6 , 15 , 16 , 18 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. The study selection process was documented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…We identified 4710 records through PubMed, EMBASE, and ScienceDirect database searches. A total of 51 articles (i.e., 33,573 patients) were selected for analysis based on the inclusion and exclusion criteria [ 6 , 15 , 16 , 18 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. The study selection process was documented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Most studies discussed the incidence of type 2 diabetes, with a minority describing type 1 diabetes. The mean age was 60-65 years in five studies [10,[16][17][18][19], whereas in others it ranged from 35 to 45 years [12,13,15]. Data regarding sex distribution were not available for two studies [11,13].…”
Section: Study Characteristicsmentioning
confidence: 98%
“…There is robust evidence suggesting that coronavirus is associated with a new diagnosis of diabetes, particularly in specific subgroups [23,[54][55][56][57][58][59][60] . Some authors reported an increase in new-onset diabetes (types 1 and 2) in the acute and post-acute Covid-19 disease, supporting a robust bidirectional relationship between SARS-CoV-2 infection and diabetes [46,47,[61][62][63][64][65][66][67][68][69] .…”
Section: Long Covid-19 As a Risk Factor For Diabetes Mellitusmentioning
confidence: 99%
“…Some authors reported an increase in new-onset diabetes (types 1 and 2) in the acute and post-acute Covid-19 disease, supporting a robust bidirectional relationship between SARS-CoV-2 infection and diabetes [46,47,[61][62][63][64][65][66][67][68][69] . In a meta-analysis of eight studies with more than 3,700 patients, Sathish et al demonstrated a pooled proportion of 14.4% for newly diagnosed diabetes in hospitalized patients for Covid-19 [56] .…”
Section: Long Covid-19 As a Risk Factor For Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation